How Does HTLV-1 Undergo Oncogene-Dependent Replication Despite a Strong Immune Response? - Gazon, Hélène; Chauhan, Pradeep; Hamaidia, Malik; Hoyos, Clotilde; Li, Lin; Safari, Roghaiyeh; Willems, Luc (Frontiers in Microbiology, 2018)
In 1987, Mitsuaki Yoshida proposed the following model (Yoshida and Seiki, 1987): " ... T-cells activated through the endogenous p40x would express viral antigens including the envelope glycoproteins which are exposed on the cell surface. These glycoproteins are targets of host immune surveillance, as is evidenced by the cytotoxic effects of anti-envelope antibodies or patient sera. Eventually all cells expressing the viral antigens, that is, all cells driven by the p40x would be rejected by the host. Only those cells that did not express the viral antigens would survive. Later, these antigen-negative infected cells would begin again to express viral antigens, including p40X, thus entering into the second cycle of cell propagation. These cycles would be repeated in so-called healthy virus carriers for 20 or 30 years or longer...". Three decades later, accumulated experimental facts particularly on intermittent viral transcription and regulation by the host immune response appear to prove that Yoshida was right. This Hypothesis & Theory summarizes the evidences that support this paradigm.